Does seeing a psychologist reduce sickness absence due to mental disorders? A quasi-experiment. (30th September 2020) - Lahti, J; Harkko, J; Sumanen, H; Piha, K; Pietiläinen, O; Mänty, M; Rahkonen, O; Lallukka, T; Kouvonen, A
Abstract: Background: Mental ill-health in young adults is a major public health and work-life problem. We examined in a quasi-experimental design whether occupational psychologist appointment can reduce subsequent sickness absence due to mental disorders among young Finnish employees. Methods: The present study was conducted among 18-39-year-old employees of the City of Helsinki using register data from the City of Helsinki and the Social lnsurance Institution of Finland. We used Wald test to compare the differences in sickness absence days due to mental disorders (ICD-10, F-diagnosed) between those treated (occupational psychologist appointment for work ability support) and the non-treated (no psychologist appointment) during a one year follow-up. The full sample (n = 2156, 84% women) consisted of employees with mental disorder diagnosed sickness absence during 2009-2014. To account for the systematic differences between the treated and non-treated, the participants were matched according to their characteristics (age, sex, occupational class, education, previous sickness absence and psychotropic medication). The matched sample included 886 participants. We excluded those with treatment before the treatment screening time (± 3 months to the end of sickness absence period), non-treated with treatment during the follow-up and those that could not be matched (lack of common support). Results: In the full sample, the mean of sickness absence days due to mental disorders was 17.7 (95% CI, 11.4, 24.1) days for those treated (n = 240) and 23.2 (95% CI, 20.5, 25.9) days for non-treated (n = 1916), difference being non-significant. The corresponding figures in the matched sample were (16.8, 95% CI, 9.5-24.1) for those treated (n = 195) and (27.8, 95% CI, 22.6-32.9) for non-treated (n = 691), difference being statistically significant (p = 0.02). Conclusions: This quasi-experiment suggests that seeing an occupational psychologist to support work ability may be reduce mental health related sickness absence. Key messages: We showed that supporting work ability at an early stage may prevent sickness absence due to mental disorders. More efforts to provide early stage support for maintaining work ability may prove useful in reducing sickness absence rates in younger employees.